2019
DOI: 10.1080/07481187.2019.1636897
|View full text |Cite
|
Sign up to set email alerts
|

Developing a practice-based research agenda for grief and bereavement care

Abstract: We aimed to identify practitioners' perspectives on current research priorities in grief and bereavement care. Grief and bereavement care providers were invited to participate in a three-phase Delphi study to create expert consensus on the top priorities for grief and bereavement research. A total of 140 participants completed Phase 1, 84 completed Phase 2, and 70 completed Phase 3. These top 10 research priorities form the basis of a practice-based research agenda for grief and bereavement care to enable rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…Studies discussing research gaps under the clinical theme comprised 56% of all papers found ( n = 14) [ 12 , 15 , 17 21 , 23 , 26 , 27 , 30 , 31 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies discussing research gaps under the clinical theme comprised 56% of all papers found ( n = 14) [ 12 , 15 , 17 21 , 23 , 26 , 27 , 30 , 31 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Last, 1 paper (4%) addressed gaps that existed within the subtheme pertaining to practitioners' understanding of grief and bereavement such as the grief process including growth and resilience, how to differentiate grief from a mental illness, and how to refer those grieving to the appropriate services [ 21 ]. As well, there was a lack of research into EoL decision-making and the relationship between advance care planning and advance directives with grief [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations